Financial burden of tuberculosis diagnosis and treatment for patients in Ethiopia: a systematic review and meta-analysis - Dawit Getachew Assefa; Zewdu Gashu Dememew; Eden Dagnachew Zeleke; Tsegahun Manyazewal; Ahmed Bedru (BMC Public Health, 2024)
Abstract Background Despite the diagnosis and treatment of tuberculosis (TB) given free of charge in many high-burden countries, the costs that patients face in the cascade of care remain a major concern. Here, we aimed to investigate the financial burden of TB diagnosis and treatment for people with TB in Ethiopia. Method For this systematic review and meta-analysis, we searched PubMed/MEDLINE, Embase, and Cochrane Center for Clinical Trials from December 1 2022 to 31 June 2023 for articles reporting the cost of diagnosis and treatment for patients regardless of their age with all forms of TB in Ethiopia. Major study outcomes were catastrophic costs, direct (out-of-pocket) pre-diagnosis, medical cost, and post-diagnosis costs, indirect (income loss) costs, coping costs, and total costs. We have used a threshold of 20% to define catastrophic costs. We used random-effects meta-analyses to calculate summary estimates of costs. R-studio software was used for analysis. The study is registered with PROSPERO: CRD42023387687. Result Twelve studies, with a total of 4792 patients with TB, were included in our analysis. At the 20% threshold of total expenses, 51% of patients (2301 participants from 5 studies, 95% CI: 36-65%, I2 = 97%) faced catastrophic costs due to bacteriologically confirmed drug-sensitive pulmonary TB. Private facility diagnosis, drug-resistance TB, TB-HIV co-infection, hospitalization, and occupation were found to be associated with catastrophic costs. Reduction in the total cost spent by the patients was associated with digital adherence interventions, community-based direct observed therapy, short-course MDR-TB treatment regimens, and active case-finding. Pre-diagnosis costs had a positive correlation with diagnosis delays and the number of facilities visited until diagnosis. Post-diagnosis costs had a positive correlation with rural residence and inpatient treatments. Conclusion Irrespective of a national policy of free TB service, more than half of TB patients are suffering catastrophic costs due to drug-sensitive pulmonary TB in Ethiopia and most of the patients spend a lot of money during the pre-diagnosis period and intensive phase, but declined drastically over time. Active case-finding, digital adherence interventions, community-based treatment, and comprehensive health insurance coverage have the potential to minimize the financial burden of TB diagnosis and treatment.